Development of School Tour Video with Wall Tracking Technique (Planar Tracker) as a Promotional Media for The Introduction of Kak Seto School Facilities - Fasya, Kemal; Padmasari, Ayung Candra (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
This study aims to assess the quality improvement of the newly developed video (School Tour Sekolah Kak Seto) compared to the old video (Fasilitas Sekolah Kak Seto) and to understand user responses to the school tour video. This research was carried out because Kak Seto School faces challenges in utilizing digital media as the primary tool in its strategy to promote the school's facilities. Previously, Kak Seto School had a video titled “Fasilitas Sekolah Kak Seto” on its YouTube Channel, focusing on introducing all the facilities available at the school. However, the video has yet to implement visual effects, the text used in the video is still fundamental, the color grading remains dark and inconsistent, and the camera/footage techniques have not met current industry standards. Therefore, developing a new School Tour video for Kak Seto School is necessary, incorporating innovations such as wall-tracking visual effects to convey the school’s facilities better. This study uses the ADDIE development method by Robert Maribe Branch, consisting of analyzing, designing, Developing, Implementing, and Evaluating. The results demonstrate that the school tour video is of higher quality than the previous video, as it has greater engagement. User responses from media and content experts rated the video as "Very Good," while respondent assessments rated it as "Good" as a promotional medium for introducing school facilities.